2010
DOI: 10.1177/0960327110361758
|View full text |Cite
|
Sign up to set email alerts
|

Wild mushroom poisonings in the Middle Black Sea region in Turkey: Analyses of 6 years

Abstract: Wild mushroom poisoning (MP) is an important medical emergency that may have serious clinical outcome. The aim of this study was to evaluate the demographic and clinical features of patients with wild MP. This study was designed retrospectively by examining files of the patients with wild MP who were admitted to Ondokuz Mayis University Emergency Department, between January 2002 and December 2007. Patients ≥16 years of age were included in the study. A total of 317 patients poisoned by wild mushrooms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 14 publications
6
38
1
5
Order By: Relevance
“…Yardan reported on 317 cases of mycetism in Turkey, without delineating which mushrooms produced toxicity, and found that common symptoms include nausea (86.6 %), vomiting (79.8 %) and diarrhea (21.1 %). Nine of these patients developed moderate to severe acute hepatic failure, with 2/9 patients having a latent phase of <6 h and the remaining 7/9 patients having a latent phase of >6 h. Thus, 22 % of patients who eventually developed hepatic failure had a latent phase of <6 h [6]. Similarly, Syed reported on three patients developing severe mushroom-induced hepatitis; 1/3 (33 %) had initial symptoms within <6 h of ingestion [15].…”
Section: Overview Of Initial General Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Yardan reported on 317 cases of mycetism in Turkey, without delineating which mushrooms produced toxicity, and found that common symptoms include nausea (86.6 %), vomiting (79.8 %) and diarrhea (21.1 %). Nine of these patients developed moderate to severe acute hepatic failure, with 2/9 patients having a latent phase of <6 h and the remaining 7/9 patients having a latent phase of >6 h. Thus, 22 % of patients who eventually developed hepatic failure had a latent phase of <6 h [6]. Similarly, Syed reported on three patients developing severe mushroom-induced hepatitis; 1/3 (33 %) had initial symptoms within <6 h of ingestion [15].…”
Section: Overview Of Initial General Assessmentmentioning
confidence: 99%
“…Approximately 100 of the known species of mushrooms are poisonous to humans, with new toxic species continually being identified [2,6,7]. Some mushrooms initially classified as edible have recently been reclassified as toxic such as Tricholoma equestre (Yellow Trich or Yellow Knight) [8].…”
Section: Overview Of Mushroomsmentioning
confidence: 99%
See 3 more Smart Citations